The effectiveness of oshibana book development for class VII students of MTs Darissulaimaniyyah plant classification materials - Manekung, Azzahra Siwi Hesti; Yasti Agustin, Haslinda (Jurnal Ilmiah BioSmart (JIBS), 2021)
This study aims to determine the effectiveness of the Oshibana book in science learning for seventh grade students of MTs Darissulaimaniyyah Plant Classification material. The research method used in this study is Research and Development (RnD) using the ADDIE model, which consists of five stages: Analyze, Design, Development, Implementaion and Evaluation. The effectiveness of the Oshibana book was measured through a feasibility test, a readability questionnaire and a trial to students using pre-test and post-test questions. The feasibility test for the Oshibana book was carried out by three validators, namely material expert validators, media expert validators and seventh grade science teachers at MTs Darissulaimaniyyah. The product trial design for students uses Quasy Experiment using amodel non equivalent control group design. The sample used was class VII B as the control class and class VII C as the experimental class, the sample was determined by purposive sampling technique. Oshibana book development process which includes special needs analysis, curriculum analysis and preparation of Oshibana book design. The results of the special needs analysis showed that 53.06% of the seventh grade students of MTs Darissulaimaniyyah did not have special learning media to study Plant Classification material so that researchers tried to develop the Oshibana book, as many as 81.63% of students agreed that the Oshibana book was developed as a learning medium. The results of the curriculum analysis of Plant Classification materials are studied in KD 3.2 about classifying living things and objects based on observed characteristics, and KD 4.2 about presenting results on classifying living things and objects around based on observed characteristics. The process of compiling the Oshibana book consists of several components, namely: cover front, introduction, table of contents, list of pictures, learning outcomes, book contents (Plant Classification materials and Oshibana materials), assignments, how to use and care for Oshibana learning media, reference lists and cover back. The results of the Oshibana book feasibility test by material experts obtained results of 72% with the criteria of being effective as a learning medium, the results of the assessment of media experts obtaining results of 81.67 with the criteria of being effective as a learning medium and the results of the assessment of the seventh grade science teacher obtaining results of 92% with the criteria very effective as a learning medium. The results of the readability test by students of MTs Darissulaimaniyyah obtained an average of 88.01% with the criteria of being very effective as a learning medium. While the results of the trial to the experimental class and control class students obtained a comparison of the average N-gain value of 0.6667 0.0185 which indicates that the average N-gain value in the experimental class using the Oshibana book is higher than the control class. who didn't use Oshibana's book. The test of the effectiveness of the Oshibana book was carried out using the Independent Sample Test, the results obtained were 0.00 0.05 indicating a significant difference. The results show that Oshibana's book is effective as a learning medium for studying Plant Classification materials.